The Effect of Agricultural Extension Access on The Performance of Smallholder Sugarcane Farmers in Indonesia - Rokhani Rokhani; Ahmad Asrofi; Ad Hariyanto Adi; Ahmad Fatikhul Khasan; Mohammad Rondhi (Universitas Muhammadiyah Yogyakarta, 2021)
Agricultural extension plays a crucial role in the Indonesian Agricultural Revitalization Program for the 2005-2025 periods, where sugarcane is one of the fourteen priority crops. The provision of an agricultural extension was aimed to increase the income and productivity of sugarcane farmers. This study aimed to evaluate the effect of agricultural extension access on smallholder sugarcane farmers' performance in Indonesia. This study used data from the 2014 Indonesian Sugarcane Farm Household Survey, consisting of 8,831 farmers. This study employed propensity score matching to estimate the effect of access to an agricultural extension on several outcome variables. These variables were gross value-added (GVA), net value added (NVA), labor productivity (LP), land productivity (LDP), net income (NI), and remuneration of family labor (ROFL). The result shows that having access to an agricultural extension increases GVA by 40.5%, NVA by 40.3%, labor productivity by 42.8%, and NI by 40.2%. However, access to agricultural extension insignificantly affects ROFL due to the differences in family working units. Also, farmers with Agricultural Extension access have 13.7% lower land productivity than non-Agricultural Extension farmers since the former has lower input use intensity than the latter. These results suggest that providing agricultural extension service is adequate to improve sugarcane farmers' economic performance.